If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3(x + -6) = 5(x + 2) + -5 Reorder the terms: 8x + 3(-6 + x) = 5(x + 2) + -5 8x + (-6 * 3 + x * 3) = 5(x + 2) + -5 8x + (-18 + 3x) = 5(x + 2) + -5 Reorder the terms: -18 + 8x + 3x = 5(x + 2) + -5 Combine like terms: 8x + 3x = 11x -18 + 11x = 5(x + 2) + -5 Reorder the terms: -18 + 11x = 5(2 + x) + -5 -18 + 11x = (2 * 5 + x * 5) + -5 -18 + 11x = (10 + 5x) + -5 Reorder the terms: -18 + 11x = 10 + -5 + 5x Combine like terms: 10 + -5 = 5 -18 + 11x = 5 + 5x Solving -18 + 11x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -18 + 11x + -5x = 5 + 5x + -5x Combine like terms: 11x + -5x = 6x -18 + 6x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 -18 + 6x = 5 + 0 -18 + 6x = 5 Add '18' to each side of the equation. -18 + 18 + 6x = 5 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 5 + 18 6x = 5 + 18 Combine like terms: 5 + 18 = 23 6x = 23 Divide each side by '6'. x = 3.833333333 Simplifying x = 3.833333333
| t+11=2t | | 10y^2+27+5y=0 | | x+14+3x+4=5x+3 | | 9x+3y=393 | | 8x+3(x-6)=5(y+2)-5 | | 8-2x=3x-5 | | 20x-16=4x+3.5 | | 3n+9=4n | | 12x^2+3-12x=0 | | 23.8=3.5n | | y=16x^2+96x | | K^2-15k+50=0 | | 15(.3-z)+14.5z=2(.5z-10) | | 5x-14=33 | | -5a=6a-44 | | 320+80x=880 | | 4P-44=-3P+100 | | K^2-15+50=0 | | 6x-120=10y | | N+4(-4-4n)=-61 | | .10x+8-x=80-10x+36 | | 3t+3=19-5t | | 9p-44=-3p+100 | | 365x/41= | | 13.6=x^3 | | 7-9a=5 | | 3(10)=6+x^2 | | 5x(73)= | | v=(1/6)*pie*h^2 | | tan(51)=12/x | | (X-6)(x-2)-5=0 | | 13t=20 |